Pendampingan Pengembangan Sumber Daya Manusia Pengelola Desa Wisata Buntu Datu di Mengkendek Tana Toraja - Wim J. Winowatan; I Nyoman Siryayasa; Irva Yulia Rohmah (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
The Community Service (PKM) program for the 2025 academic year in Buntu Datu Tourism Village, Mengkendek District, Tana Toraja Regency, aims to enhance the human resources (HR) capacity in managing community-based tourism villages. This village has great tourism potential, supported by basic facilities such as gazebos, halls, camping areas, and food stalls that cater to tourists’ activities. However, tourism village management still faces challenges such as limited facilities, low digital promotion skills, lack of innovation in developing tourist attractions, and suboptimal use of village funds to support the tourism sector. The PKM implementation methods involve socialization, training, interviews, field observations, and Focus Group Discussions (FGD) with the community, village officials, and tourism awareness groups (Pokdarwis). Through a participatory approach, this activity successfully improved the community's understanding of destination management, tourist services, facility management, and digital promotion strategies via social media and online platforms. Although the impact was limited due to the relatively short duration of the assistance, the activity received high appreciation from the community and emphasized the importance of collaboration between the community, government, and academics. It is hoped that follow-up programs will strengthen local capacity, enhance tourism attractiveness, and support the sustainable economic welfare of the Buntu Datu Tourism Village community.